Penerapan Technology Academy Dalam Meningkatkan Soft Skill Melalui Program Studi Independen Kampus Merdeka Pada PT Revolusi Citra Edukasi (Revou) - Silmi Rahmani; Jojok Dwiridotjahjono (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The Merdeka Campus Program is a program organized by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia, one of the programs is the Independent Study in partnership with PT Revolusi Citra Edukasi which is called RevoU Technology, this program has the aim that the participants gain experience and knowledge about technology academy which is useful for the world of work, by participating in an independent study program the participants will meet various students throughout Indonesia as well as mentors who are experienced in their fields, participants will also know the impact of implementing technology academy on companies such as the impact of product management, digital marketing , data analyst and software engineering